An Energy-Efficient Comparator With Dynamic Floating Inverter Amplifier - Xiyuan TANG; Shen, Linxiao*(Corresponding Author); Kasap, Begum; Yang, Xiangxing; Wei Shi; Mukherjee, Abhishek; Pan, David Z.; Sun, Nan (IEEE Journal of Solid-State Circuits, 2020)
This article presents an energy-efficient comparator design. The pre-amplifier adopts an inverter-based input pair powered by a floating reservoir capacitor; it realizes both current reuse and dynamic bias, thereby significantly boosting gm/ID and reducing noise. Moreover, it greatly reduces the influence of the process corner and the input common-mode voltage on the comparator performance, including noise, offset, and delay. A prototype comparator in 180 nm achieves 46-μV input-referred noise while consuming only 1 pJ per comparison under a 1.2-V supply. This represents greater than seven-time energy efficiency boost compared with a strong-arm (SA) latch. It achieves the highest reported comparator energy efficiency to the best of our knowledge.